Faktor-Faktor yang Berhubungan dengan Kecelakaan Kerja pada Proyek Pembangunan Mal di PT X Tahun 2025 - Layli Agusti Wachid; Decy Situngkir; Putri Handayani (Universitas Muhammadiyah Manado, 2025)
Work accidents remain a significant issue in the construction sector and can be caused by various factors, including basic causes (knowledge and length of service), lack of control (supervision), and immediate causes (housekeeping). A preliminary study indicated that 53% of respondents had experienced accidents of varying severity. This study aims to analyze factors related to work accidents in the mal construction project at PT X in 2025. The research employed an analytic cross-sectional design with 84 workers selected using simple random sampling. Data were collected using a questionnaire and analyzed through univariate and bivariate methods with the chi-square test. The study was conducted from May to July 2025. Univariate results showed the highest proportion in workers who had experienced accidents (57 respondents; 67.9%), had high knowledge (52 respondents; 61.9%), long work experience (51 respondents; 60.7%), high supervision (52 respondents; 61.9%), and conducive housekeeping (49 respondents; 58.7%). Bivariate analysis revealed significant relationships between knowledge (p=0.000), supervision (p=0.043), and housekeeping (p=0.044) with work accidents, while length of service (p=0.596) showed no relationship. These findings are expected to serve as a basis for preventing work accidents at PT X.